A MEMÓRIA PRÉ-HISPÂNICA DE Malinche - O PATRIMÔNIO CULTURAL DO POVO MEXICA - Sara Lelis de Oliveira (Nepan editor, 2019)
This work presents the literary work Malinche (2006), by the Mexican writer Laura Esquivel, as narrative that remembers part of the cultural heritage of the Mexicas (also known as Aztecs), people that dominated almost all the Mesoamerican territory before the Castilian invasion in century XVI. The specific rescue of this culture origina-tes from the starting locus of the narrative: the participation of the indigenous Malinalli, popularly known under the epithet la Malinche, as the interpreter of the conversations between the Mexican rulers and the Castilian conquistador Hernán Cortés during the process of the fall of Tenochtitlán (1519 – 1521), city of the Mexica Empire. The re-creation of the confrontation between cultures caused by the historical event brings to light several elements of the pre-Hispa-nic culture due to the contact of Malinalli with the Castilian culture, in which both cultures contrast, but also because of the difficulties she encountered to translate Nahuatl into Spanish and vice versa.